Pilot symbol aided channel estimation for spatial modulation-OFDM systems and its performance analysis with different types of interpolations - Doğan, Hakan; Panayırcı, Erdal; ACAR, YUSUF (Springer, 233 Spring St, New York, Ny 10013 USA, 2017)
Spatial modulation orthogonal frequency division multiplexing (SM-OFDM) system has been recently proposed as an alternative for multiple-input multiple-output (MIMO)-OFDM systems to increase spectral efficiency by keeping a low-complexity implementation. In the literature, SM-OFDM systems assume a perfect channel state information (P-CSI) available at the receiver for coherent detection and the channel estimation problem is not considered. It is clear that the channel estimation is a critical issue on the performance of SM-OFDM systems. In this paper, a frame structure where pilot symbols are typically interspersed with data symbols among the sub-carriers to aid the channel estimation is considered. Then the pilot symbol aided channel estimation (PSA-CE) technique with different interpolations is proposed for the SM-OFDM systems. It is shown that in the proposed PSA-CE, equidistantly spaced pilot symbols allow to reconstruct the channel response by means of interpolation if the spacing of the pilots is sufficiently close to satisfy the sampling theorem. Linear, nearest neighbor, piecewise cubic Hermite and the low-pass interpolations are investigated to explore trade-off between complexity and performances. We show that the low pass interpolator yields better performance than the other interpolation techniques for selected cases such as higher order modulations. The results validate the potential of the proposed PSA-CE estimation applying to SM-OFDM systems.
Keywords: Multiple-input multiple-output (MIMO); Orthogonal frequency division multiplexing (OFDM); Spatial modulation (SM); Channel estimation; Interpolation; Fading Channels; Diversity; Capacity